Blossom Drop, Reduced Fruit Set, and Post-Pollination Disorders in Tomato - Monica Ozores-Hampton; Fnu Kiran; Gene McAvoy (EDIS)
Blossom drop and reduced fruit set in tomato can seriously impact yields. Growers in Florida routinely experience such problems and inquire about the cause and possible preventative measures to reduce flower loss and improve yields. The problem can be frustrating and difficult to manage in some situations. This 6-page fact sheet was written by Monica Ozores-Hampton, Fnu Kiran, and Gene McAvoy, and published by the UF Department of Horticultural Sciences, July 2012.